Tax administration and national economic sustainability - Nurudeen, Abdulfatai Olanrewaju; Onifade, Hakeem O.; Siyanbola, Trimisiu. Tunji; Ojurongbe, Jubril O. (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
Despite the abundance of natural deposits and active participation in the global digital economic market, Nigeria continued to borrow finance her annual budget. It is obvious that non oil income of Nigeria, inclusive of taxes is at depleted level. This study therefore appraises the effect of digital tax, tax administration and tax legal frameworks on sustainable economic development in Nigeria conceptually. The study concluded that digital tax and tax administration have effects on attainment of sustainable economic development in Nigeria. The study recommends that the FIRS, with required resources, should ensure efficient operations, while the federal government should review the legal and technical capacity of the FIRS in line with the requirement to combat digital tax evasion and enhance optimum compliance to achieve a sustainable economic development.